Towards smart storage for repository preservation services - Hitchcock, S; Tarrant, D; Brown, A; O'Steen, B; Jefferies, N; Carr, L (Edinburgh University Library, 2010)
The move to digital is being accompanied by a huge rise in volumes of (born-digital) content and data. As a result the curation lifecycle has to be redrawn. Processes such as selection and evaluation for preservation have to be driven by automation. Manual processes will not scale, and the traditional signifiers and selection criteria in older formats, such as print publication, are changing. The paper will examine at a conceptual and practical level how preservation intelligence can be built into software-based digital preservation tools and services on the Web and across the network ‘cloud’ to create ‘smart’ storage for long-term, continuous data monitoring and management. Some early examples will be presented, focussing on storage management and format risk assessment.